The notes : Ronald Reagan's private collection of stories and wisdom - Reagan, Ronald (Harper, 2011)
From the bestselling editor of "The Reagan Diaries" come the newly disclosed notebooks of Ronald Reagan that bring to light his most intimate thoughts and favorite quotations.